Multivariate analysis on the effectiveness of monetary and fiscal policies in Fiji - Dahalan, Jauhari; Jayaraman, T. K. (Universiti Utara Malaysia, 2006)
By utilising a Cointegrating Vector Autoregressive Model, this paper assesses the relative effectiveness the fiscal and monetary policies on growth. It is observed that government expenditure has the strongest effect on Fiji's national income which significantly explains Fiji's GDP error variance even after a three year period with regard to the effect of shocks, we observed that the national income impulse respons to the one standard error shock among all macroeconomic variables, i.e. government expenditure and foreign assets, which is not permanent but transitory.